Validitas Soal Matematika Tipe PISA Konteks Covid-19 - Sintia Andita; Liana Septy; Harisman Nizar; Rieno Septra Nery (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2020)
This study was carried out to test the validity of math problems in Al-Hijrah High School 10th grade students with a maximum age of 15 year. The goal of this study was to obtain the most recent PISA type math questions in the context of Covid-19 with an accurate level of validity as determined by expert review and one-to-one. The trial was conducted on three students with different abilities in the classroom while still applying health protocols. This research was conducted through a development method that was divided into two stages, namely preliminary and formative evaluation, which included self-evaluation and prototyping (expert review and one-to-one). This research produces instrumen kits, namely grids, scoring rubrics, question cards and of course the prototype 2 question sets that are feasible to use. Keyword: PISA, Expert Review, One-to-one, Mathematics